Chassin's Operative Strategy in General Surgery An Expositive Atlas - Scott-Conner, Carol E.H (Springer New York : Imprint: Springer, 2014)
The Fourth Edition of Chassin's Operative Strategy in General Surgery: An Expositive Atlas is designed to expand this comprehensive and unique general surgery reference while remaining true to the special character of the work. This unique text continues to provide an emphasis on surgical strategy that is unmatched by other textbooks of surgical technique. It continues to comprehensively cover all non-vascular operations commonly performed by general surgeons. As always, Chassin's explains the conceptual basis of each operation, outlines strategies to avoid common pitfalls, and carefully describes and beautifully illustrates the technical steps of each operation. The Fourth Edition has been expanded and updated by adding both new procedures and new features. A significant new feature, "Documentation Basics" has been added to each chapter, providing a bulleted list of key features that need to be listed in the operative note to accurately describe extent of procedure and enhance accuracy of coding. General surgery continues to evolve.  Procedures are added and many operations are done through new minimal access approaches. However, as a surgeon may be called upon to perform an operation that has become rare, Chassin's unique "legacy" material has been retained for reference. In addition, 17 new chapters have been added, including 4 new chapters on colorectal surgery. Over 1100 elegant illustrations and new radiographs accompany detailed textual explanations. Mo re than ever, Chassin's Operative Strategy in General Surgery: An Expositive Atlas, Fourth Edition is an indispensable reference for all surgical residents and practicing surgeons.